Você está na página 1de 11

f, g : [1 , 3] → R f ( x ) = x +

f, g : [1, 3] R f (x) = x + 2 g (x) = x 2 + x S (f, P )

S (g, P ) .

f : [2, 5] R f (x) = x 2 + 2 S(f, P ) .

f (x) = 5 x 2 , x [1, 2].

x 4 + 2

y

=

x = 0 x = 1 y = 0.

3 (x 2 2x)dx.

1

4 (x 2 1)dx.

0

f (x) =

x 3 + 1,

x [0, b], b > 0

f (x) = e x x, x = 1 x = 2.

x = y 2 y, y [0, 2].

f : [a, b] R

(a) f a f (x)dx = 2

(b)

(c)

a

a

0

f a f (x)dx = 0.

a

f (x)dx.

T o F ),

20 1 t(t 12)(t 24), t t = 0

6

T(t) =

f x = 0 x = t A(t) = t 3 , t > 0.

f x f (t)dt = [f (x)] 2 x R + .

0

x

f : R R g : R R g(x) = 2

x

3

f (t)dt.

g : R R dg dt

f(x) = x

0

dg

dt

(t)dt x R.

f

f [a, b],

a, b R,

a < b.

f g.

f g

f

: [0, 1) R f (x) =

1

1 x 2 1 f (x) dx

0

x 2

2 xe x 2 dx

1

1

1

(a)

(b)

x 3

+ 9 dx

(d)

(g)

1

0

2

1

x sin xdx

1 ( √ x + √ x + 3
1
( √ x +
√ x +
3

x ) dx

4

(e)

3

4

4

3

1 x 2 dx
+

x 1

(h) π tan xdx

0

3

(c)

(f )

(i)

π tan 2 x sec 2 xdx

0

4

3

0

x

x + 1 dx

4

1

x

2 + 4x dx

(a)

(b)

1

0

( x + x

0

x ) dx (e) −∞ xe x dx

1

3

− 0 √ x ) dx ( e ) ∫ −∞ xe x dx 1 3

2 x 2 ln(x)dx

0

(f )

−∞ xe |x4| dx

(c) +

1

(d)

0

2

2

2 cos ( x ) dx

1

x

1

1

1 x 2 dx

(g) 5

1

1

5

x dx

(h) +e x dx

0

(i)

4

0

x

16

x 2 dx

(j) +

0

xe x dx

(k) +

1

1

x

x

2

1 dx

(l)

1

0

1 x dx

1

1

(m)

−∞

e x dx

1

(n)

1

(o)

1

0

1

4 dx

x

1

3 dx

x

+

(p)

2

1

(x + 1) 2 dx

f (t) = 700e 5 t t

1

p +

1

1

p dx

x

p R +

e

1

x(ln

x) p dx

(a) +xe x 2 dx

1

(d) 1 x ln xdx

0

(g) +

1

ln(x 1 )

x

2

dx

+

(b)

−∞

arctan x x 2 + 1

dx

π

2

(c)

−∞

sin(2x)dx

(e) 9

0

e

x

x

dx

(f ) π

0

(h) 6

3

1

x 3 x 2 9 dx

cos x 1 sin x

dx

(i) 3 x 2 6x + 13dx

1

f

L(f (x)) = +e sx f (x)dx,

0

s R

(a) f(x) = e ax

(b) f (x) = cos x

(c) f (x) = sin x

x > 0

Γ(x) = +t x1 e t dt.

0

(a)

Γ(1) Γ(2).

(b)

n Γ(n + 1) = nΓ(n).

(a)

(b)

(c) y = x 2 + 9 y = 3 x.

(d) y = sin x y = x sin x,

(e) 28 y 5x = 0 x y 2 = 0 y = 2x y = 0.

y = cos x x

y x = 6, y x 3 = 0

y = sin x

= 0 x = π 2 . 2y + x = 0.

x = 0 x = π 2 .

A =

0

2

[ (y + 6) ( 4 y 2 ) ] dy.

(a)

(b)

(c)

(d)

(i) x

y = x + 3

x = y 2 + 3.

2x + y

= 2,

x y = 1

(ii) y.

7x y = 17.

y = x 2 1, y = 2 2 y = 32x 2 .

x

y + x = 6,

y = x

y + 2 = 3x.

A = 2 [ ( 2x 2 ) ( x )] dx + 4

1

2

2

[( 62 15x

4

) (

2

x )] dx.

y

x

4 1 ,

y = x, y = x 2 y =

x.

y. y
y.
y

x

y = k y = x 2 y = 9

R

√ 2 2 A = ∫ − √ 2 2
2
2
A = ∫
√ 2
2

(a) y;

( 1 x 2 2x 2 ) dx.

(b)

0

A = 2 π 3 sin t(3 sin t)dt 2

π

0

3 sin t(2 sin t)dt.

P (0, 0) a (0, a), x. x = a(t sin t) y = a(1 cos t), t [0, 2π].

x 3 + y 3 = a 2 3 a = 5.

2

2

(a)

r = 3 cos θ r = 1 + cos θ;

(b)

r = 1 + cos θ r = 1;

(c)

r = sin θ r = 1 cos θ;

(d)

r 2 = cos(2θ) r 2 = sin(2θ);

r = 6 cos θ r = 2(1 + cos θ).

r = 4 + 4 cos θ r = 6.

r = 1 + cos θ r = 2 cos θ.

r = sin(2θ) r = sin θ.

r = sin(2θ) r = cos(2θ).

r = sin(2θ) r =

3 cos(2θ),

= cos(2 θ ) . r = sin(2 θ ) r = √ 3 cos(2 θ

R r = 2 cos θ r = 4 sin θ r = 1.

(a)

R;

(b)

R.

r = 1

r = 2 cos(2θ)
r = 2 cos(2θ)

1

r = 2e 4 θ

r = sin(3θ)

R. r = 1 r = 2 cos(2θ) 1 r = 2 e 4 θ r
R. r = 1 r = 2 cos(2θ) 1 r = 2 e 4 θ r

r = cos(3θ)

I

= 2 [ 1 2 π sin 2 θdθ +

0

6

1

2

π

6

π

4

cos 2 (2θ)] .

r = 2 + 2 cos θ,

r = 4 cos(3θ) r = 2.

sin 2 θdθ + 0 6 1 2 ∫ π 6 π 4 cos 2 (2

x =

x = 3 + t 2

x = 5t 2

x = e t cos t

r = e θ , 0 θ 2π;

3 y 3 + 4y , 2 y 5;

1

1

y = 6 + 2t 2 , 1 t 5; y = 2t 3 , 0 t 1;

y = e t sin t, 0 t π ;

2

1

r = cos 2 2 θ, 0 θ π;

A(2, 3)

B(0, 3) t, x(t) = 1 + (3 t)

y(t) = 3 (3 t).

t, x(t) = 2 cos t + 2t sin t y(t) = 2 sin t 2t cos t. t = 0 t = π

2 .

x(t) = 4t 3 + 1 y(t) = 2t 9

2

A(5, 2)

B(33, 32 2).

t = 0 t = 4,

x(t) = 1 + 2 cos(3t 5 2 ) y(t) = 5 2 sin(3t

5

2

).

x(t) = 3e t cos 6t y(t) = 3e t sin 6t

t [0, +),

y x
y
x

r = 3 sin θ r = 3 cos θ,

l = π 48 cos 2 θ + 48 sin 2 θdθ +

0

6

π

6

π

2

16 sin 2 θ + 16 cos 2 θdθ.

r = 1 + sin θ r = 3 sin θ.

yx 2 = 1, x 1,

x.

x 2

a 2 + y b 2

2

= 1

x 2 + (y b) 2 = a 2 x, a < b.

y = 4 x, 3y = x y = 0, x;

y = |x| + 2 y = x 2 x = 2 x = 1 x;

y = x 2

y = 1 x 2

x + y = 3

y = 2, y = 2; x y = 1, y = 3; y + x 2 = 3, x = 2.

y = e x

x, x 0, y = 2.

x = 3, x = 3 9y 2 4x 2 = 36 x.

R y,

V

= π 2

1

3

[ ( 7 3y

2

) 2 (

1

y

) 2 ] dy.

R R y = 3.

R y = x 3 x = y 3 .

R.

R y.

R y = 1.

y = x 2 4 y = x 2

x

y = 2

x = 3.

R y = x 3 y = 2x, y = 2 x.

R x.

R x = 1.

r h

V

= πr 2 h

3

.

a V = 4 πa 3 .

3

S (f,

S (f,

S (f,

S (f,

2

P ) = 8 + n

S (g, P ) = 38

+ 10

4

133

3

n

+ 3n 2

+ 6n 2

1

3

6n 2

1

S (f, P) = 8

3

1

2n

30n 4

P ) = 175

3

P ) = 8

P ) = 11 5

133

2n

3

3 + 2n

1

+ 2n + 3n 2

2

3

76

3

1

4 b 4 + b e 2 e 1

8

3

1

6n 2

u = x

18, 9 o F

f (x)

f (t) = 3t 2

= x

2

g (1) = 2

1 f

0

(x) dx =

1

2 π

(a)

(d)

1

2 e 1

1

2 e 2

sin 1 cos 1

(g) 3, 202

(a)

1

3

(b)

(c)

(d) 1 4 π

8

3

ln 2 8

9

sin 1

(b)

(e) 0, 405

(h)

3 10 4 2

2

3

ln 2

) 0 , 405 ( h ) 3 √ 10 − 4 √ 2 2 3

(e)

(f ) 8

(g) 4

(h) 1

1

(i) 4

(j) 1

(k)

(l) 2

1

2 π

1 (c) (f ) 8 3 3 (i) 3 √ 2 2 (m) e (n)
1
(c)
(f ) 8
3
3
(i) 3 √ 2
2
(m) e
(n) nao˜
existe
(o)
nao˜
existe
(p) nao˜
existe

3500 m 3

p > 1.

2 1 e −1 (a) (b) 0 (c) nao˜ existe (d) (e) 2e 3 −
2 1 e −1
(a)
(b) 0
(c) nao˜
existe
(d)
(e) 2e 3 − 2
(f) 0
− 1 4
(g)
− 1
(h) 0, 027
(i) 4, 59
1
s
1
(a)
para s > a
(b)
para s > 0
(c)
s − a
s 2 + 1
s 2 + 1
(a) Γ(1) = 1,
Γ(2) = 1
(a) 2 √ 2 − 2
(b) 22
(c) 125
(d) 2 − 2 sin 1
(e) 17
6
y
x
(c) 32−4 √ 2
(a) 125
(b) 16
(d) 23
6
3
6
) − (
( 62 − 4y
2
( 62 − 4y ) − ( √ 2y
A = ∫ 2
y ) dy + ∫ 8
) dy
15
15
2
1
2
2

(a)

( 2 A = ∫ 2 ( x 2 − x ) dx + ∫
(
2
A = ∫ 2 ( x 2 − x ) dx + ∫ 1+ √ 17
1
2

x 1 x ) dx

4

(b) A =

1

17 1 2 x − 1 − x ) dx 4 ( b ) A =

1+ 17 (y y) dy +

2

4

( y + 4

y 1+ √ 17 2
y
1+
√ 17
2

y ) dy

k =

9

3

4

(a) A = 2

0

π

4

(b) A =

3π

4

√ 2 1 2 √ y √ 4 dy + 2 ∫ √ 2 2
√ 2
1
2
√ y
4
dy + 2 ∫
2
2
2

1 y 2 dy

√ 2 t 2 dt 2t 2 dt

sin 2 tdt

y 2 dy √ 2 t 2 dt − sin 2 tdt − ∫ − √

2

2

y x
y
x

3a 2 π

3πa 2

8

(a) 5π

4

(b)

4 5 π 2

(c)

2 1 (π 2)

(d) 1 − √ 2 2
(d) 1 − √ 2
2

(e) 6π 8 2

para s > 0

4π

18 3 4π

π

2

1

4 π − − 1

π

2

3

16 3

A =

0

π 2 ( 3 cos 2θ) 2 +

4 1
4
1

0

π

6

2 1 (sin 2θ) 2 +

π

6

π

4

1 2 ( √ 3 cos 2θ) 2 dθ
1
2 ( √ 3 cos 2θ) 2 dθ

(a) A =

1

2

arctan

arcsin

1

4

1

2

(16 sin 2 θ 1)+

1

2

π

3

arctan

1

2

( 4 cos 2 θ 1 )

1 π π arctan 2 3 3 (b) l = ∫ 4dθ + ∫ 2
1
π
π
arctan
2
3
3
(b) l = ∫
4dθ + ∫
2 2dθ + ∫
1
1
arcsin
arctan
arcsin
4
(a) 9 √ 3
− π
(b)
4e 9π
4
8e 5π + 4e π
4
4
8
4

1

4

(c) π 1

8

4

A

=

1

2 π

0

9

+

[ (2 + 2 cos θ) 2 (4 cos 3θ) 2 ] + 1 2

π

9

1

2 π

0

9

4+

1

2

π

9

π

6

(4 cos 3θ) 2

π

2

[ (2 + 2 cos θ) 2 4 ]

(a) 1563 40 (d) √ 2e π 2
(a) 1563
40
(d)
√ 2e π
2

2

(b) 24 5

(e) 2(1 e 2π )

(c) 68

5 ( e ) √ 2(1 − e − 2 π ) ( c ) 6

27 34 250

27

(f) 2

π

π 2

4

c ) 6 8 2 7 √ 34 − 2 5 0 27 ( f )

352 22 250

27

27

192

333.

3 3π + π

1

2

y x π π 6 2 l = 2 ∫ √ 9 cos 2 θ
y
x
π
π
6
2
l = 2 ∫
√ 9 cos 2 θ + 9 sin 2 θdθ + 2 ∫
π
0
6

cos 2 θ + (1 + sin θ) 2

π

3

4πab 2

3

2π 2 a 2 b

32π

7

2

(a) 3 π

2

π

(b) 92π

5

410 π 6π ln 6

27

(c)

64 √ 2π 15
64 √ 2π
15

(d) 162 π

5

(e)

1 2 π

l = 1 ( 1 + 9x 4 + 1 +

1

1

9 x

4

3

) dx

V

=

32

35 π

V

0

= π

1

(1 x) 2 (1 x 3 ) 2 dx + π 1 (1 x 3 ) 2 (1 x) 2 dx

3

0

3

2

(a) V = π 1 (x 4 9x 2 + 4x + 12)dx

(c)

V = π 4 (y + 8 + 4 y + 4)dy π

4

0

3

(b) V

2

= π

1

(20 13x 2 x 4 + 8x)dx

0

(y + 8 4 y + 4)dy π

3

(y 2 + 8y + 16)dy

(a) 134 π

189

(b) V

= π 1 (1 + y) 2 ( 1 + y ) 2 dy + π

0

3

2

1

4 (3 y) 2 ( 1 + y ) 2 dy

3

2

y y = h x, x [r, r] y [0, h].

x 2 + y 2 = a 2

r